Inserción social de desmovilizados: Una percepción de la sociedad Colombiana (2023)
The conquest to achieve peace in Colombia is the bet in which the sectors of their community converge; therefore, public and private companies expect to assume the responsibility of designing and deploying programs of social and economic reintegration, in favor of those who have been part of the armed conflict in this country. The objective of this work is to analyze the perception that society assumes vis-a-vis the demobilized and their inclusion in the business sector, given that there is currently a large amount of this collectivity in search of reincorporation into civil life. The research was developed under a qualitative and quantitative approach. The population studied was constituted by 279,552 inhabitants between the ages of 19 and 59, located in the urban area of the city of Ibague, Colombia. The findings have detected the presence of aversion towards the demobilized and their possible employment relationship. In conclusion, it is noted that the public policies in economic matters from the Colombian government, should strengthen the traditional relations of discrepancy in Colombian society, because their splits reside in social disconformities. © 2019, Universidad del Zulia.